Workshop on Format Conversion - Mazić, Bogoljub (Infotheca - Journal for Digital Humanities, 2024)
Alan Hopkinson led a workshop on Format Conversion which was one of the key topics to be covered under the Tempus project UM_JEP-16059-2001 "Building a Cooperative Academic Library Network in Serbia" The session was divided into five sections.